Application and Mechanisms of Triptolide in the Treatment of Inflammatory Diseases—A Review - Yuan, Kai; Li, Xiaohong; Lu, Qingyi; Zhu, Qingqing; Jiang, Haixu; Wang, Ting; Huang, Guangrui; Xu, Anlong (Frontiers in Pharmacology, 2019)
Bioactive compounds from medicinal plants with anti-inflammatory and immunosuppressive effects have been emerging as important sources of drugs for the treatment of inflammatory disorders. Triptolide, a diterpene triepoxide, is a pharmacologically active compound isolated from Tripterygium wilfordii Hook F (TwHF) that is used as a remedy for inflammatory and autoimmune diseases. As the most promising bioactive compound obtained from TwHF, triptolide has attracted considerable interest recently, especially for its potent anti-inflammatory and immunosuppressive activities. Over the past few years, an increasing number of studies have been published emphasizing the value of triptolide in the treatment of diverse inflammatory disorders. Here, we systematically review the mechanism of action and the therapeutic properties of triptolide in various inflammatory diseases according to different systematic organs, including lupus nephritis, inflammatory bowel disease, asthma, and rheumatoid arthritis with pubmed and Embase. Based on this review, potential research strategies might contribute to the clinical application of triptolide in the future.